Holding Two Worlds, Keeping Art Alive: ArtVoice As a Method to Explore Indigenous Knowledges in Zenadth Kes - Francis Nona; Britta Wigginton (Health Promotion Journal of Australia, 2026)
ABSTRACT Climate change is already impacting the livelihoods and lifeways of Indigenous peoples globally, including in the Zenadth Kes (Torres Strait) communities of the continent now called Australia. To date, Indigenous perspectives and Knowledges remain underexplored in public health scholarship. Few culturally grounded, place‐based methods exist to engage respectfully with these sensitive issues. In this article, we present the findings of ArtVoice , an arts‐based, community‐driven qualitative method rooted in Indigenous epistemologies and relational ways of knowing. ArtVoice , as a ‘method‐in‐place’, invited community members to express their experiences, hopes and concerns about climate change through creative artworks. Field visits and yarns were guided by cultural protocols, Indigenous self‐determination and cultural authority supported by a participatory approach. We present the reflections on the process and practice of applying ArtVoice in decolonising and culturally responsive ways, while upholding local protocols for managing and re‐representing Knowledges. This article attempts to decolonise health promotion research while simultaneously honouring Indigenous Knowledge systems. Elucidating the tensions and opportunities of these distinct knowledge systems helps us document the complexities of decolonising research practice and dissemination.